Interrelation and Distinction between Legislative Drafting and Policy - Khadka, Arjun Kumar (Prashasan: The Nepalese Journal of Public Administration, 2023)
Drafting is part of the legislative process, which in turn is part of the policy process. It is even sometime compared or linked to a child's game of Snakes and ladders. Snakes and ladders are game of chance where legislative drafting is game of skill. Moreover, legislative drafting requires abundance of knowledge of the language, its grammar, and the technical requirements of the form of legislation and perform the task in a non-partisan manner and keeping totally away from political controversies. On the other hand, a policy relates to government goal for achieve the methods and principles. But, policy document is not a law. Thus, policy sets out the goals and planned activities of a concern ministry and department, but laws set a standard procedures and principles that must be followed. If a law is disregard, the violator will punish as prescribed by the laws. So, law is binding and mandatory compared to policy, which means that legislative process is more valuable in practice.